PENGARUH FASILITAS KERJA, BEBAN KERJA DAN TEAMWORK TERHADAP KINERJA PENGAWAI DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KABUPATEN LUWU SEKTOR WALENRANG - Kartila, Kartila; Elsa, Elsa; Tobade, Marni Yulianti; Marsal, Marsal; Ardhana, Muhammad Anugrah (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of work facilities, workload, and teamwork on the performance of employees at the Luwu Regency Fire and Rescue Service, Walenrang Sector. The background of this study is based on the importance of service quality and firefighter preparedness, which are significantly influenced by the availability of work facilities, the workload faced, and the ability to work together as a team. The research method used was a quantitative approach, with questionnaires distributed to employees as respondents. Data were analyzed using multiple linear regression to determine the influence of each independent variable on employee performance. The results showed that work facilities had a positive and significant effect on employee performance, meaning that the better the facilities available, the higher the performance. Workload had a significant negative effect on performance, indicating that a high workload tends to decrease employee effectiveness and productivity. Meanwhile, teamwork had a significant positive effect on performance, where solid teamwork can improve coordination, effectiveness, and success in carrying out rescue tasks. Simultaneously, these three variables significantly influenced employee performance. This study concludes that improving employee performance in the Walenrang Sector of the Luwu Regency Fire and Rescue Service can be achieved through the provision of adequate work facilities, proportional workload management, and strengthening teamwork among team members.